EVOLUTION OF CONCEPTUAL APPROACHES IN MANAGEMENT TO CRISIS MANAGEMENT UNDER CONDITIONS OF UNCERTAINTY - MOISEIEV, Kyrylo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the evolution of conceptual approaches in management, from crisis management in the early 20th century to the present day. Based on a comparative analysis of the works of classical management thinkers (A. Fayol, E. Mayo), Nobel laureates (H. Simon, J. Stiglitz, R. F. Engle, D. Kahneman), founders of modern ideas and contemporary scholars (P. Drucker, R. Thaler, I. Mitroff), the study traces the transformation of approaches and ideas in crisis management within management — from resource-based and rational planning to behavioral models, emotional leadership, proactive thinking, and systemic readiness for uncertainty. The article focuses on key shifts in management paradigms: from reactive reaction to strategic foresight; from centralized control to adaptability and viability; from rational optimization to heuristic decision-making under conditions of information deficit. Particular attention is given to the concepts of  “limited rationality”, “change management” and “management in a turbulent environment”, “decision-making under uncertainty” and the “five-component framework of crisis management” as the fundamental elements of the modern crisis management approach. The author proposes viewing the evolution of the crisis management concept under uncertainty through the prism of four stages, each accompanied by an authorial definition. Each stage corresponds to the development of the management idea discussed in the article. These are the stages of administrative stability, organizational adaptation, cognitive flexibility, and systemic viability. The summarization of scientific approaches has allowed the author to propose an update of the definition of crisis management in providing a company’s viability under uncertainty as a holistic, dynamic system of managerial actions that supports a company’s viability through early risk detection, organizational learning, the development of flexible strategies, and the maintenance of adaptability.The article outlines prospects for further research in the direction of integrating digital tools, cognitive models, and developing a competence-based approach to enhancing the crisis management potential of companies.
Keywords: crisis management; evolution of approaches; management under uncertainty; organizational viability; system’s approach